ANALYSIS OF HUMAN RESOURCE READINESS FOR THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AT DR. H. ABDUL MOELOEK REGIONAL GENERAL HOSPITAL IN 2025 - Olivia Anjani; Galuh Ismayanti (LLDIKTI Wilayah X, 2026)
The implementation of Electronic Health Records (EHR) is part of the digital transformation of the healthcare system, which requires comprehensive human resource (HR) readiness. This study aims to critically analyze HR readiness for the implementation of EHR at Dr. H. Abdul Moeloek General Hospital by 2025. The method used is qualitative with a descriptive-interpretive approach through in-depth interviews with healthcare workers, medical records staff, and the IT team. Analysis was conducted using thematic techniques based on a critical analysis approach. The results of the study indicate that HR readiness is in a transitional and asymmetrical phase, characterized by disparities in digital competencies, resistance to change, and weak internalization of digital culture. Compared to previous studies, these findings suggest that HR readiness issues are not merely a matter of training but are also related to organizational structure, work culture, and change management. This study concludes that the failure of EMR implementation is likely to occur if digital transformation is not accompanied by human transformation